Debye-Waller Thermal Parameter of Crystalline Materials as a Determinant of their Properties in various Phases: An Overview. (2015) - Butt, M.Z.
Abstract: In late nineteen eighties, the Neutron Diffraction Commission of International Union of Crystallography initiated a project to compile the most accurate values of the Debye-Waller thermal parameter B of cubic elements as well as of cubic binary compounds. N. M. Butt and co-workers recommended such values for 22 cubic elements (Butt et el 1988) and 52 cubic binary compounds (Butt et al., 1993) determined at room temperature by diffraction methods using x-rays, neutrons, γ – rays, and high voltage electrons. Since then, several attempts have been made to correlate numerous general, thermal, metallurgical, mechanical, and crystal defect properties of cubic structure crystals with their room-temperature Debye-Waller thermal parameter B not only in solid, liquid and vapor phases but also in plasma state. The correlations between microscopic parameter B and macroscopic or bulk properties of crystals have been found to be systematic. This connection between micro and macro aspects of materials has set new trends in the interpretation of the behavior of crystalline materials.